2020 السلطة التنفيذية في الجزائر في ظل التعديل - نبيل يعقوبي; سفيان كواشي (My University, 2022)
Summary: Arris's father aims to demonstrate the status of the executive branch under the Algerian constitutional amendment. 2020, in order to reach this goal, we have decided to address, at the outset, the different concepts of the executive branch that Most agree with the broad notion that the executive branch's functions are primarily to implement the will Regardless of the owner's individual or group, if under contemporary parliamentary systems the will is enforced people through the implementation of people's deputies. Until the executive branch performs its mandated functions, it has broad powers and powers. Whether it is their internal organization or their relations with the other authorities, this is the basis of the constitutions. From here the executive branch's relationship with the rest of the authorities begins to operate in harmony and cooperation. together with other powers, particularly legislative in the parliamentary system, and to a lesser extent in the semi-presidential system It may amount to dependence under the unity of authority, as in the assembly system, and on the contrary we find it fully independent in the presidential system. To further capture the subject of our study, we have studied the executive branch's impact on successive Algerian constitutions. Through it, we have concluded that the executive branch under the 2020 constitutional amendment continues to hold a superior position. Despite the changes that have been affected, whether by internal reorganization through the possibility of appointing a First Minister or President a government, or by reviewing its relations with other authorities by introducing parliamentary oversight mechanisms and The Constitution focuses on its actions as well as curtailing some of its powers, but this has not risen to the point that There is a real balance between the executive and the rest of the authorities, considering that what has been developed has not affected the The superior status of the executive branch, which still enjoys in addition to its inherent competencies as policy maker The country's general internal and external powers and powers vis-à-vis other functional authorities As the power to dissolve parliament without spelling, legislating with orders in addition to powers of a judicial nature such as appointments to Qualitative judicial positions and the power to issue amnesties and reduce or replace penalties. This leads us to argue that the 2020 constitutional amendment, while seeking to strike a real balance between power, The executive and the rest of the authorities, however, maintained the distinct status of the executive in comparison .......................... اﻟﻤﻠﺨص: ﺘﻬدف ﻫذﻩ اﻟد ارﺴﺔ اﻟﻰ ﺒﻴﺎن ﻤﻛﺎﻨﺔ اﻟﺴﻠطﺔ اﻟﺘﻨﻔﻴذﻴﺔ ﻓﻲ ظﻝ اﻟﺘﻌدﻴﻝ اﻟدﺴـــﺘوري اﻟﺠزاﺌــري ٬ 2020 وﻟﻠوﺼﻝ اﻟﻰ ﻫذا اﻟﻬدف إرﺘﺄﻴﻨﺎ اﻟﺘطرق ﺒداﻴﺔ إﻟﻰ ﺒﻴﺎن اﻟﻤﻔﺎﻫﻴم اﻟﻤﺨﺘﻠﻔﺔ ﻟﻠﺴﻠطﺔ اﻟﺘﻨﻔﻴذﻴﺔ اﻟﺘﻲ ﺘﺘﻔق ﻓﻲ ﻤﻌظﻤﻬﺎ ﻓﻲ اﻟﻤﻔﻬوم اﻟواﺴﻊ اﻟذي ﻤَؤداﻩ أن اﻟﺴﻠطﺔ اﻟﺘﻨﻔﻴذﻴﺔ ﺘﺘﻤﺜﻝ ﻤﻬﺎﻤﻬﺎ أﺴﺎﺴﺎ ﻓﻲ ﺘﻨﻔﻴذ اﻹرادة ﺒﻐض اﻟﻨظر ﻋن ﺼﺎﺤﺒﻬﺎ ﻓردا ﻛﺎن أو ﺠﻤﺎﻋﺔ ٬ وان ﻛﺎﻨت ﻓﻲ ظﻝ اﻷﻨظﻤﺔ اﻟﻨﻴﺎﺒﻴﺔ اﻟﻤﻌﺎﺼرة ﺘَُﻨﻔْذ اﻹرادة اﻟﺸﻌﺒﻴﺔ ﻋن طرﻴق ﺘﻨﻔﻴذ ﻤﺎ ﻴﺸرﻋﻪ ﻨواب اﻟﺸﻌب. و ﺤﺘﻰ ﺘﻘوم اﻟﺴﻠطﺔ اﻟﺘﻨﻔﻴذﻴﺔ ﺒﺄداء اﻟﻤﻬﺎم اﻟﻤﻨوطﺔ ﺒﻬﺎ ﻓﻬﻲ ﺘﺘﻤﺘﻊ ﺒﺴﻠطﺎت و ﺼﻼﺤﻴﺎت واﺴﻌﺔ ﺴواء ﺘﻌﻠق اﻷﻤر ﺒﺘﻨظﻴﻤﻬﺎ داﺨﻠﻴﺎ أو ﺒﻌﻼﻗﺎﺘﻬﺎ ﻤﻊ ﺒﺎﻗﻲ اﻟﺴﻠطﺎت وﻫذا ﻤﺎ ﻨﺠد أﺴﺎﺴﻪ ﻓﻲ اﻟدﺴﺎﺘﻴر. و ﻤن ﻫﻨﺎ ﺘﺒدأ ﻋﻼﻗﺔ اﻟﺴﻠطﺔ اﻟﺘﻨﻔﻴذﻴﺔ ﺒﺒﺎﻗﻲ اﻟﺴﻠطﺎت ﻓﻨﺠدﻫﺎ ﺘﻌﻤﻝ ﻓﻲ اﻨﺴﺠﺎم وﺘﻌﺎون ﺠﻨﺒﺎ إﻟﻰ ﺠﻨب ﻤﻊ ﺒﺎﻗﻲ اﻟﺴﻠطﺎت وﺨﺼوﺼﺎ اﻟﺘﺸرﻴﻌﻴﺔ ﻓﻲ اﻟﻨظﺎم اﻟﺒرﻟﻤﺎﻨﻲ ٬ وﺒدرﺠﺔ أﻗﻝ ﻓﻲ اﻟﻨظﺎم ﺸﺒﻪ اﻟرﺌﺎﺴﻲ وﻗد ﺘﺼﻝ ﻟدرﺠﺔ اﻟﺘﺒﻌﻴﺔ ﻓﻲ ظﻝ وﺤدة اﻟﺴﻠطﺔ ﻛﻤﺎ ﻓﻲ اﻟﻨظﺎم اﻟﺠﻤﻌوي وﻋﻠﻰ اﻟﻨﻘﻴض ﻤن ذﻟك ﻨﺠدﻫﺎ ﻤﺴﺘﻘﻠﺔ ﺘﻤﺎﻤﺎ ﻓﻲ اﻟﻨظﺎم اﻟرﺌﺎﺴﻲ. وﻟﻺﺤﺎطﺔ أﻛﺜر ﺒﻤوﻀوع دراﺴﺘﻨﺎ آﺜرﻨﺎ دراﺴﺔ اﻟﺴﻠطﺔ اﻟﺘﻨﻔﻴذﻴﺔ ﻓﻲ اﻟدﺴﺎﺘﻴر اﻟﺠزاﺌرﻴﺔ اﻟﻤﺘﻌﺎﻗﺒﺔ اﻟﺘﻲ ﻤن ﺨﻼﻟﻬﺎ ﺘوﺼﻠﻨﺎ اﻟﻰ أن اﻟﺴﻠطﺔ اﻟﺘﻨﻔﻴذﻴﺔ ﻓﻲ ظﻝ اﻟﺘﻌدﻴﻝ اﻟدﺴﺘوري 2020 ﻻ زاﻟت ﺘﺤﺘﻝ ﻤﻛﺎﻨﺔ ﻤﺘﻔوﻗﺔ رﻏم اﻟﺘﻌدﻴﻼت اﻟﺘﻲ ﻤﺴﺘﻬﺎ ٬ ﺴواء ﺒﺈﻋﺎدة ﺘﻨظﻴﻤﻬﺎ داﺨﻠﻴﺎ ﻤن ﺨﻼﻝ إﻤﻛﺎﻨﻴﺔ ﺘﻌﻴﻴن وزيرا أوﻻً او رﺌﻴس ﺤﻛوﻤﺔ ٬ أو ﻤن ﺨﻼﻝ إﻋﺎدة اﻟﻨظر ﻓﻲ ﻋﻼﻗﺎﺘﻬﺎ ﺒﺒﺎﻗﻲ اﻟﺴﻠطﺎت ﺒﺎﺴﺘﺤداث آﻟﻴﺎت رﻗﺎﺒﻴﺔ ﺒرﻟﻤﺎﻨﻴﺔ و دﺴﺘورﻴﺔ ﺘﻨﺼب ﻋﻠﻰ أﻋﻤﺎﻟﻬﺎ إﻀﺎﻓﺔ اﻟﻰ ﺘﻘﻠﻴص ﺒﻌﻀﺎ ﻤن ﺼﻼﺤﻴﺎﺘﻬﺎ ٬ ﻏﻴر أن ﻫذا ﻟم ﻴرﻗﻰ ﻟدرﺠﺔ أﻨﻪ ﻴﺤدث ﺘوازن ﺤﻘﻴﻘﻲ ﺒﻴن اﻟﺴﻠطﺔ اﻟﺘﻨﻔﻴذﻴﺔ وﺒﺎﻗﻲ اﻟﺴﻠطﺎت ﻋﻠﻰ إﻋﺘﺒﺎر أن ﻤﺎﺘم إﺴﺘﺤداﺜﻪ ﻟم ﻴؤﺜر ﻋﻠﻰ ﻤﻛﺎﻨﺔ اﻟﺴﻠطﺔ اﻟﺘﻨﻔﻴذﻴﺔ اﻟﻤﺘﻔوﻗﺔ ٬ اﻟﺘﻲ ﻻ ازﻟت ﺘﺘﻤﺘﻊ إﻀﺎﻓﺔ إﻟﻰ إﺨﺘﺼﺎﺼﺎﺘﻬﺎ اﻷﺼﻴﻠﺔ ﻛرﺴم اﻟﺴﻴﺎﺴﺔ اﻟﻌﺎﻤﺔ ﻟﻠﺒﻼد داﺨﻠﻴﺎ و ﺨﺎرﺠﻴﺎ ﺒﺼﻼﺤﻴﺎت وﺴﻠطﺎت ﻛﺒﻴرة ﻓﻲ ﻤواﺠﻬﺔ ﺒﺎﻗﻲ اﻟﺴﻠطﺎت ﻋﻀوﻴﺎ وظﻴﻔﻴﺎ ﻛﺴﻠطﺔ ﺤﻝ اﻟﺒرﻟﻤﺎن دون ﺘﺴﺒﻴب ٬ واﻟﺘﺸرﻴﻊ ﺒﺄواﻤر إﻀﺎﻓﺔ ﻟﻠﺴﻠطﺎت ذات اﻟطﺎﺒﻊ اﻟﻘﻀﺎﺌﻲ ﻛﺎﻟﺘﻌﻴﻴﻨﺎت ﻓﻲ اﻟﻤﻨﺎﺼب اﻟﻘﻀﺎﺌﻴﺔ اﻟﻨوﻋﻴﺔ وﺴﻠطﺔ إﺼدار اﻟﻌﻔو وﺘﻘﻠﻴص اﻟﻌﻘوﺒﺎت أو إﺴﺘﺒداﻟﻬﺎ. ﻫذا ﻤﺎ ﻴدﻓﻌﻨﺎ ﻟﻠﻘوﻝ ﺒﺄن اﻟﺘﻌدﻴﻝ اﻟدﺴﺘوري 2020 رﻏم ﺴﻌﻴﻪ ﻹﺤداث ﺘوازن ﺤﻘﻴﻘﻲ ﺒﻴن اﻟﺴﻠطﺔ اﻟﺘﻨﻔﻴذﻴﺔ و ﺒﺎﻗﻲ اﻟﺴﻠطﺎت إﻻ أﻨﻪ ﺤﺎﻓظ ﻋﻠﻰ اﻟﻤﻛﺎﻨﺔ اﻟﻤﺘﻤﻴزة ﻟﻠﺴﻠطﺔ اﻟﺘﻨﻔﻴذﻴﺔ ﻤﻘﺎرﻨﺔ ﺒﺒﺎﻗﻲ اﻟﺴﻠطﺎت و ﺨﺼوﺼﺎ اﻟﺘﺸرﻴﻌﻴﺔ. ................................... Résumé : Le père d’Arris vise à démontrer le statut du pouvoir exécutif en vertu de l’amendement constitutionnel algérien. 2020, afin d’atteindre cet objectif, nous avons décidé d’aborder, dès le départ, les différents concepts du pouvoir exécutif qui La plupart sont d’accord avec l’idée générale selon laquelle les fonctions du pouvoir exécutif consistent principalement à mettre en œuvre la volonté Quel que soit l’individu ou le groupe du propriétaire, si dans les systèmes parlementaires contemporains la volonté est appliquée par la mise en place de sous-ministres du peuple. Jusqu’à ce que l’exécutif remplisse ses fonctions, il dispose de vastes pouvoirs. Que ce soit leur organisation interne ou leurs relations avec les autres autorités, c’est la base des constitutions. A partir de là, la relation du pouvoir exécutif avec le reste des autorités commence à fonctionner en harmonie et en coopération. avec d’autres pouvoirs, notamment législatifs dans le système parlementaire, et dans une moindre mesure dans le système semi-présidentiel Il peut s’agir d’une dépendance vis-à-vis de l’unité d’autorité, comme dans le système d’assemblage, et au contraire nous la trouvons totalement indépendant dans le système présidentiel. Pour mieux saisir le sujet de notre étude, nous avons étudié l’impact du pouvoir exécutif sur les constitutions algériennes successives. Nous en sommes venus à la conclusion que le pouvoir exécutif, en vertu de la modification constitutionnelle de 2020, conserve une position supérieure. Malgré les changements qui ont été touchés, que ce soit par une réorganisation interne par la possibilité de nommer un premier ministre ou un président un gouvernement, ou en examinant ses relations avec d’autres autorités en instaurant des mécanismes de surveillance parlementaire et La Constitution se concentre sur ses actions et réduit certains de ses pouvoirs, mais cela n’a pas atteint le point où Il y a un véritable équilibre entre l’exécutif et le reste des autorités, étant donné que ce qui a été développé n’a pas affecté Le statut supérieur du pouvoir exécutif, qui jouit encore en plus de ses compétences inhérentes en tant que décideur Compétences générales internes et externes du pays vis-à-vis d’autres autorités fonctionnelles En tant que pouvoir de dissoudre le Parlement sans orthographe, légiférer avec des ordres en plus des pouvoirs de nature judiciaire, comme les nominations à Positions judiciaires qualitatives et pouvoir d’imposer des amnisties et de réduire ou de remplacer les sanctions. Cela nous amène à soutenir que la modification constitutionnelle de 2020, tout en cherchant à établir un véritable équilibre entre le pouvoir, L’exécutif et le reste des autorités, cependant, ont maintenu le statut distinct de l’exécutif en comparaison